PELATIHAN AKUNTANSI DESA BAGI PARA APARATUR PEMERINTAH NEGERI DI WILAYAH KECAMATAN LEITIMUR SELATAN KOTA AMBON - Usmany, Paul; Loupatty, Linda Grace; Usmany, Alfrin E. M. (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
Community ServiceCommunity Service (PkM) is basically the social responsibility of the higher education academic community to help the community solveacademic community of higher education to help the community in solvingproblems faced or in developing their potentials.that they have. Within this framework, the community service activities ofcommunity service activities of the Faculty of Economics and Business Pattimura University organized "Village Accounting Training forState Government Apparatus in the South Leitimur District of Ambon City".The objectives of organizing this PkM are to: 1) improveinsights, knowledge, and abilities of the state government apparatus through alternativeaccounting learning alternatives as a basis for understanding in organizing accounting records according to generally accepted accounting principles and preparing financial reports.accounting principles and prepare financial statements; and 2) provide knowledge, and technical accounting skills to civil servants so that they can be accountable to the government.apparatus so that they can accurately account for the realization of the APBDes implementation.accurately. ActivityThis training was held for 2 days, from August 30 to 31, 2023, and was attended by 32 (64%) of the target audience.(64%) of the target audience. The implementation of this training activity was carried outusing lecture, discussion, question and answer, and simulation methods. Activities"Village Accounting Training for State Government Officials in the District of Leitimur Selatan Leitimur Selatan Ambon City" went well. All participants were enthusiasticattended the event until the end and felt the benefits of this training.The participants also considered that the training was important and verynecessary for local government officials and other stakeholders. The participants also hoped that similar training can be conducted intensively again in the future with more participants, and more applicable material design related to the participants' daily tasks. Keywords: Community Servicecommunity service, village accounting, public government apparatus, and South Leitimur Sub-district.Leitimur Selatan.